Polymers Included in Natural Materials to Treat Acne - Mahmoud, Sally Saher Lutfi; Gaidan, Fatima Imran Mohammed; Mahdi, Yaqeen abaas hasen; Abd, Zeena Khalel Turky; Hamaadi, Jehan Hamad salih (American Journal of Biomedicine and Pharmacy, 2025)
Biopolymers, synthetic polymers and their derivatives are commonly used in medicine and pharmacology due to significant advances in polymer chemistry and technology. The dynamic development of medical engineering has promoted. Recently, special attention of scientists has focused on medical biopolymers, especially those used for drug delivery systems, and therapeutic systems. The polymer was used as a major tool in controlling the rate of drug release from the formulations. It is also used as an employee agent to mask the bait. It is also used as a stabilizing agent and a protective agent in oral drug delivery. Polymers can bind solid dose molecules and can also alter the flow properties of liquid dose. Extended applications of polymers in drug delivery have been investigated because these polymers display unique properties that are not found in other materials. Polymers are molecules that are formed in the form of large chains and contain different functions and can also mix with materials with large and low molecules. Therapeutic applications have opened new avenues for exciting polymeric drugs, because specially designed polymers are able to provide drug materials to target diseased cells and tissues with the culture of those drugs according to the specific drugs that cause collateral damage. Recently, special attention has been drawn to chemical and biocompatible polymers, because they have the advantage of being easily degraded and non-toxic.